Being born under adverse economic conditions leads to a higher cardiovascular mortality rate in life: Evidence based on inidviduals born at different stages of the business cycle - Gerard J. van den Berg; Gabriele Doblhammer-Reiter; Kaare Christensen (Institute for Labour Market Policy Evaluation (IFAU), 2008)
We connect the recent medical and economic literatures on the long-run effects of early-life conditions, by analyzing the effects of economic conditions on the individual cardiovascular (CV) mortality rate later in life, using individual data records from the Danish Twin Registry covering births since the 1870s and including the cause of death. To capture exogenous variation of conditions early in life we use the state of the business cycle around birth. We find a significant negative effect of economic conditions early in life on the individual CV mortality rate at higher ages. There is no effect on the cancer-specific mortality rate. From variation within and between monozygotic and dizygotic twin pairs born under different conditions we conclude that the fate of an individual is more strongly determined by genetic and household-environmental factors if early-life conditions are poor. Individual-specific qualities come more to fruition if the starting position in life is better.
Keywords: 330; longevity; genetic determinants; health; recession; life expectancy; cardiovascular disease; cancer; lifetimes; fetal programming; cause of death; developmental origins; Lebensverlauf; Soziale Lage; Konjunktur; Gesundheitsrisiko; Sterblichkeit; Dänemark